Gastrocnemius Medialis Muscle Geometry and Extensibility in Typically Developing Children and Children With Spastic Paresis Aged 6–13 Years - Weide, Guido; Huijing, Peter A.; Bar-On, Lynn; Sloot, Lizeth; Buizer, Annemieke I.; Becher, Jules G.; Harlaar, Jaap; Jaspers, Richard T. (Frontiers in Physiology, 2020)
Gait of children with spastic paresis (SP) is frequently characterized by a reduced ankle range of motion, presumably due to reduced extensibility of the triceps surae (TS) muscle. Little is known about how morphological muscle characteristics in SP children are affected. The aim of this study was to compare gastrocnemius medialis (GM) muscle geometry and extensibility in children with spastic paresis (SP) with those of typically developing (TD) children and assess how GM morphology is related to its extensibility. Thirteen children with SP, of which ten with a diagnosis of spastic cerebral palsy and three with spastic paresis of unknown etiology, (mean age 9.7±2.1 years; GMFCS: I-III) and fourteen TD children (mean age 9.3±1.7 years) took part in this study. GM geometry was assessed using 3D ultrasound imaging at 0 Nm and 4 Nm externally imposed dorsal flexion ankle moments. GM extensibility was defined as its absolute length change between the externally applied 0 and 4 Nm moments. Anthropometric variables and GM extensibility did not differ between the SP and TD groups. While in both groups, GM muscle volume correlated with body mass, the slope of the regression line in TD was substantially higher than that in SP (TD=3.3 ml/kg; SP=1.3 ml/kg, p<0.01). In TD, GM fascicle length increased with age, lower leg length and body mass, whereas in SP children, fascicle length did not correlate with any of these variables. However, the increase in GM physiological cross-sectional area as a function of body mass did not differ between SP and TD children. Increases in lengths of tendinous structures in children with SP exceeded those observed in TD children (TD=0.85 cm/cm; SP=1.16 cm/cm, p<0.01) and even exceeded lower-leg length increases. In addition, only for children with SP, body mass (r=-0.61), height (r=-0.66), muscle volume (r =0.66), physiological cross-sectional area (r=0.59), and tendon length (r=-0.68) showed a negative association with GM extensibility. Such negative associations were not found for TD children. In conclusion, physiological cross-sectional area and length of the tendinous structures are positively associated with age and negatively associated with extensibility in children with SP.